Underfill fatigue life enhancement by means of rubber and elastomer additives - Yamaguchi, Hiroshi; Enomoto, Toshiaki; Sato, Toshiyuki (2018 International Conference on Electronics Packaging and IMAPS All Asia Conference (ICEP IAAC), 2018)
Fatigue life is an essential issue for underfill (UF). To improve its fatigue properties, various composites have been studied. We prepared UF samples each with rubber or elastomer additives and conducted fatigue tests on them to obtain fatigue curves. Besides, finite elementary method (FEM) analyses on thermal cycle testing of flip chip packages (FCPKG) were conducted to calculate strain and stress caused in the process of one cycle of heat variation. These values were applied to the fatigue curves to predict UF fatigue lives. The results confirmed that rubber and elastomer additives enhance fatigue lives of UF as for repeated low load. FE-SEM observation of surfaces implies that fracture mode of UF with elastomer is not brittle but ductile. We determined that the process can be effective as a method to predict fatigue life.